Sex hormones and allergies: exploring the gender differences in immune responses - Gutiérrez-Brito, Jesús Alberto; Lomelí-Nieto, José Álvaro; Muñoz-Valle, José Francisco; Oregon-Romero, Edith; Corona-Angeles, Jazz Alan; Hernández-Bello, Jorge (Frontiers in Allergy, 2025)
Allergies are closely associated with sex-related hormonal variations that influence immune function, leading to distinct symptom profiles. Similar sex-based differences are observed in other immune disorders, such as autoimmune diseases. In allergies, women exhibit a higher prevalence of atopic conditions, such as allergic asthma and eczema, in comparison to men. However, age-related changes play a significant role because men have a higher incidence of allergies until puberty, and then comes a switch ratio of prevalence and severity in women. Investigations into the mechanisms of how the hormones influence the development of these diseases are crucial to understanding the molecular, cellular, and pathological aspects. Sex hormones control the reproductive system and have several immuno-modulatory effects affecting immune cells, including T and B cell development, antibody production, lymphoid organ size, and lymphocyte death. Moreover, studies have suggested that female sex hormones amplify memory immune responses, which may lead to an excessive immune response impacting the pathogenesis, airway hyperresponsiveness, inflammation of airways, and mucus production of allergic diseases. The evidence suggests that estrogens enhance immune humoral responses, autoimmunity, mast cell reactivity, and delayed IV allergic reactions, while androgens, progesterone, and glucocorticoids suppress them. This review explores the relationship between sex hormones and allergies, including epidemiological data, experimental findings, and insights from animal models. We discuss the general properties of these hormones, their effects on allergic processes, and clinical observations and therapeutic results. Finally, we describe hypersensitivity reactions to these hormones.